Incidencia del control interno en la gestión del inventario de la asociación de limpieza de Los Ríos, en el cantón Babahoyo, periodo 2022-2023. - Santillán Herrera, Alexi Sebastián (2024)
The study conducted at the Asociación de Limpieza de Los Ríos during the 2022-2023 period revealed several weaknesses in inventory management, directly affecting operational and administrative efficiency. The main problems identified included expired products, discrepancies between recorded and physical stock, lack of necessary materials for daily operations, and unauthorized product withdrawals. These issues highlight deficiencies in internal control procedures, which prevent the accurate management of inventory. The analysis demonstrated that the use of manual methods, such as spreadsheets and limited physical audits, contributed to a high margin of human error and a lack of real-time visibility into inventory status. This has hindered timely decision-making and increased the risk of financial losses due to insufficient control over product flow. The implementation of corrective measures, such as an automated inventory management system, has shown positive results by reducing the number of expired products, improving the concordance between records and physical stock, and decreasing unauthorized withdrawals. Additionally, the introduction of stricter procedures and clear assignment of responsibilities for each transaction has significantly reduced problems related to product shortages and unauthorized withdrawals. By standardizing processes and continuously training staff, resource utilization has been optimized, contributing to more efficient and reliable inventory management. In conclusion, improving internal control is essential for ensuring operational effectiveness, profitability, and transparency in inventory management at the Asociación de Limpieza de Los Ríos.